Application of DNA mini-barcoding and infrared spectroscopy for the authentication of the Italian product "bottarga". (March 2021) - Frigerio, Jessica; Marchesi, Claudio; Magoni, Chiara; Saliu, Francesco; Ballabio, Davide; Consonni, Viviana; Gorini, Tommaso; De Mattia, Fabrizio; Galli, Paolo; Labra, Massimo
Abstract: Tuna "Bottarga" is an artisanal food speciality prepared from the roe of Bluefin Tuna ( Thunnus thynnus). Due to the recent restriction of Tuna catches fixed by EU, cheaper substitutes from yellowfin tuna ( Thunnus albacares) are currently available in the mass distribution. Since the product is sold sliced or grated, morphological distinctive features may be lost, and fraudulent substitution is possible. In this study we tested DNA mini-barcoding and infrared spectroscopy as tools to trace its authenticity. A certified chemical standard, fresh (n = 4) and processed (n = 11) ovarian identified by the morphological observation of the tuna catches, commercial bottargasamples (n = 5) and artificial aged aliquots of all these samples (n = 50) were used in the experiments. The results showed that infrared spectroscopy failed in the taxonomic distinction, whereas enabled PLS-DA classification of aged samples (and thus the identification of fresh prepared artisanal products) with model non-error rate in fitting equal to 0.96, and 0.89 in cross-validation. Conversely, DNA mini-barcoding with mtDNA control region, success in species identification (100% maximum identity by the standard comparison BLAST approach against GenBank), regardless the processing state of the product. Highlights: Fraudolent substitution of seafood products is possible. A combined molecular and spectroscopic approach was applied as tool to authenticity control of Bluefin tuna roe. DNA mini-barcoding provided the taxonomical authentication of the products, regardless the processing. PCA analysis applied to Infrared spectra enable a discrimination based on storage condition.